The role of the Constitutional Council of France in the organisation and conduct of the elections of the President of the French Republic - Antonov, Alexey V. (Journal of the Belarusian State University. Law, 2021)
This article is devoted to one of the powers of the Constitutional Council of the French Republic – the control of the regularity of the election of the president of the republic. The procedure and powers of this body at each stage of the election process are described in detail. The author concludes that the combination of three elements of competence in one body – control, organisational and jurisdictional, hardly corresponds to the modern legal tradition. At the same time, the Constitutional Council, despite the individual cases of deviations from the rules mentioned in the article, is fulfilling its mission with dignity and integrity.
Keywords: President of the French Republic; Constitutional Council of the French Republic; Constitution of the French Republic; oversee the regularity of the election of the president of the republic